Optimalisasi pencatatan keuangan Klinik Pratama Selamat melalui program sosialisasi dan pelatihan pencatatan akuntansi - Dailibas, Dailibas; Chaerudin, Chaerudin; Setyorini, Christina Tri (Nur Science Institute, 2025)
Limitations in preparing financial reports are a common challenge for Micro, Small, and Medium Enterprises (MSMEs), including the healthcare sector. Klinik Pratama Selamat faces similar obstacles in recording financial transactions systematically and structured. This community service activity aims to provide socialization and training on accounting records to improve the understanding and ability of the management of Klinik Pratama Selamat in conducting accounting records, including preparing financial reports. The methods used in this activity are socialization and mentoring. The results of this activity showed an increase in participants' understanding of the importance of financial records and how to make financial records correctly and according to applicable accounting standards, as well as the ability to prepare accurate and transparent reports. This activity is expected to improve the quality of financial management of Selamat Primary Clinic and support its operational sustainability.